Pendampingan Optimalisasi Media Sosial untuk Meningkatkan Produktivitas di Kalangan UMKM Warga Kecamatan Lumbang Probolinggo - Ibad, M. Nashoihul; Dewantara, Muhammad Iqbal (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This community service program aims to assist Micro, Small, and Medium Enterprises (MSMEs) in Lumbang District, Probolinggo Regency, in optimizing the use of social media to increase business productivity. The focus of the training is to provide participants with understanding and skills regarding effective digital marketing strategies, especially through the Instagram platform. With the training module titled